EFFECT OF ORGANIZATIONAL CITIZENSHIP BEHAVIORS AS A MODERATION BETWEEN SERVANT LEADERSHIP ON EMPLOYEE PERFORMANCE - Yuniarto, Prayogo (Universitas Brawijaya, Indonesia, 2018)
This study aims to investigate the complexities effect of servant leadership and employee performance and the moderating role of organizational citizenship behaviors (OCB) on the relationship between servant leadership and employee performance. Servant leadership measured using empowerment, love, humility, trust, and vision. This Study collected data from 154 respondents using questionnaire method. The analysis tool in this research is Structural Equation Modeling (SEM) using generalized structured component analysis (GeSCA). From the results of model testing is known that the required goodness of fit test value is FIT, AFIT, GFI, SRMR, and NPAR with using GeSCA. Based on the results of hypothesis testing are known: there is a positive influence on the servant leadership to the employee performance. OCBstrengthen the role of the relationship between servant leadership for employee performance. Suggestions for future research is to develop research by adding indicators or adding other variables on other organization with different characteristic.